جهود الخديوي إسماعيل التعليمية في مصر والسودان - خالد خلف وفاء (مجلة كلية التربية, 2020)
When Khedive Ismail been crowned to Egypt on 1863. Education system of Mohammed Ali been collapsed but at era of Khedive Ismail have rebuild the education system then the budget of education amonnted (80,000) Egyptian pond and the important thing is the free education system, and establishing of girls schools which were the first of its kind of ottoman state, all of it been come true, the number of pupils of the primary school (11.802) pupils studying at (4685) school after it was (185) school only at 1863, it was studying (100,000) pupils, and the education in situations have been increased and this development expanded to each the army. There was a special school for each pregade of the arm. Therefore according to the military report at 1872, there were just (42) not education personat the army. Ismail kept going with his education reforms which started by Mohammed Ali Pasha where the popular education of Arabic language have been developed and gave a huge efforts and reopened the old schools that been closed at the era of Abbas Pasha, plus a new schools been opened.